A business performance measurement system for incubated startups - Casado, Frank; Siluk, Julio; Neuenfeldt Júnior, Alvaro Luiz; Ataide, Lucas de; Quiroga, Oscar Daniel (Revista de Administração da UFSM, 2020)
Purpose – The development of a model to measure and assess the performance of start-ups in a standard incubation process, based on 99 critical success factors identified as the most relevant for the context. Design/methodology/approach – A total of three sequential steps were developed to reach the objectives proposed (Problem overview; modeling; and usage). The model was tested on four development stage incubation processes start-ups and three maturity stage incubation processes start-ups, located at the Technological Incubator of Santa Maria (ITSM). Findings – After the modeling phase, compromising results were found for only one developed stage start-up evaluated. Meanwhile, for the maturity stage, all three evaluated start-ups are competitive. To support the strategic decision-making process, the scores obtained were stratified to diagnose which perspective may compromise the performance of each start-up. Originality/value – This research proved to be adaptable to the decision context, thus being amenable to be used in different scenarios. The model presented in this work is composed of a systematic tool suitable to support the continuous improvement and learning processes for incubated start-ups, in specific to measure and assess the performance of start-ups.